Biosocial predictors and blood pressure goal attainment among postmenopausal women with hypertension - Kandasamy, Geetha; Subramani, Thangamani; Sam, Gigi; Almanasef, Mona; Almeleebia, Tahani; Shorog, Eman; Alshahrani, Asma M.; Hmlan, Amjad; Al Suhaym, Atheer Y.; Prabahar, Kousalya; Veeramani, Vinoth Prabhu; Amirthalingam, Palanisamy (Frontiers in Cardiovascular Medicine, 2024)
Abstract Objectives: Women in postmenopausal states may not maintain blood pressure (BP) in the same way as men, despite the fact that most women follow their treatment plans and prescriptions better than men. Biological and lifestyle factors influence the progression of hypertension in post-menopausal women (PMW). This study aimed to determine biosocial predictors associated with reaching the target BP in PMW with hypertension. Methods: A prospective observational study was conducted in general medicine department at Karuna Medical College Hospital, Kerala, India. The definition of BP goal attainment was set by the VIII Joint National Committee 2014 (JNC VIII) guidelines. Multivariate logistic regression analysis was used to analyse biosocial predictors like educational status, employment status, body mass index, number of children, age at menarche, age at menopause and number of comorbidities associated with BP goal achievement. Results: The patients with 56.4% achieved BP goal on monotherapy and 59.7% achieved on combination therapy. Level of education (OR = 1.275, 95% CI: 0.234–7.172), employment status (OR=0.853, 95% CI: 0.400–1.819), age at menopause (OR = 1.106, 95% CI: 0.881–1.149), number of children (OR=1.152, 95% CI: 0.771–1.720), BMI (OR=0.998, 95% CI: 0.929–1.071) and number of co-morbidities (OR = 0.068, 95% CI: 0.088–1.093) have not shown a significant relationship and age at menarche (OR=1.577, 95% CI: 1.031–2.412), showed a significant association with BP goal attainment among hypertensive postmenopausal women. Conclusion: Half of the hypertensive postmenopausal women did not achieve the BP goal. Intervention is required to expand screening coverage and, under the direction of medical professionals, there should be plans to improve hypertension control and increase knowledge of the condition.